UNSOLVED ISSUES IN BULGARIAN TOURISM - Rozalin YANEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Through processing the information on existing methods of lease, problematic situations on lease agreements of agricultural-purpose land held in shared ownership are studied in the article. The existing methods of rent under land lease agreements in case of joint lessor by the municipal districts of the Saratov region are considered thoroughly. It is established that the most common is the rent-in-kind. According to the study, it is advisable to use the monetary form of rent for improving the financial-and-economic results of agricultural production of business entities. The result of the study is the development of the method of differentiated rent. Using the SWOT-analysis the proposed method is scientifically substantiated, measures for threat manageability putting advantages of the method strengths, use of favorable opportunities to overcome its weaknesses, reduction of the adverse impact of the combination "weaknesses – threats" are determined. The recommended method reflects the land rent received in specific production conditions, taking into account the product yield, allows lessees and lessors to invest free funds. The method of calculating the differentiated rent is based on determining the anticipated net operating income depending on the level of agricultural crop productivity, land market price taking into account the discount rate. This method is focused on agricultural producers who are lessees and lessors of agricultural-purpose land held in shared ownership, executive authorities and managing bodies of agro-industrial complex.